Multivariate analyses of DNA index, p62c-myc, and clinicopathological status of patients with ovarian cancer. Issue 6 (June 1998) - Curling, M; Stenning, S; Hudson, C N; Watson, J V
Abstract : AIM: To determine if either DNA index or p62c-myc is an independent prognostic variable in ovarian cancer. METHODS: Multivariate and univariate analyses of the relation between DNA index, p62c-myc, FIGO stage, histological type, tumour grade, completeness of surgery, and patient survival in ovarian cancer were examined. RESULTS: Multivariate analysis showed significant association of survival only with stage and grade. There was no relation between survival and DNA index. CONCLUSIONS: DNA index is not an independent prognostic variable in ovarian cancer.